Problematika Produk Hukum Daerah Terkait Perizinan di Pemerintah Kota Jambi - Fajri, Ikhwannul; Azed, Abdul Bari; Muslih, M (Legalitas: Jurnal Hukum, 2024)
Implementation of Jambi City Regional Regulation Number 9 of 2010 concerning the Implementation of One-Stop Integrated Services (PTSP), is currently no longer relevant to the dynamics of changing times and the contents of the Regional Regulation do not contain a chapter that regulates supervision as regulated in Minister of Home Affairs Regulation Number 25 of 2021 concerning DPMPTSP and BKPM Regulation Number 2 of 2021 concerning Guidelines and Procedures for Supervising Risk-Based Business Licensing. This study explains the implementation of legal products related to licensing in Jambi City Government, the problems of legal products related to licensing in Jambi City Government and the impact of the implementation of legal products related to licensing in Jambi City Government.